Optimising the use pigging data in pipeline reliability assessment - Md. Noor, Norhazilan (2007)
Pigging in the context of pipelines refers to the practice of using devices known as "pigs" to perform various maintenance operations. This is done without stopping the flow of the product in the pipeline.